Analytical Work on Missing Persons Search: Modern View of the Problem: Trabajo analítico sobre la búsqueda de personas desaparecidas: Vías modernas de los problemas - Nykyforchuk, Dmytro; Okhrimenko, Ivan; Chemerys, Dmytro; Blikhar, Viacheslav; Kisil, Zoryana; Shevchuk, Oksana (Political Questions, 2022)
The article is devoted to the analysis of law enforcement agencies’ activities to search for missing persons. The purpose of the study is to examine the peculiarities of the analytical work of law enforcement agencies on missing person’s search. The methodological bases are general scientific and special scientific methods and techniques of scientific knowledge (systemic, formal-logical, structural-functional, sociological, historical and axiological). It is concluded that the criteria for law enforcement agencies to search for missing persons are the general state of search work, search for certain categories of missing persons, trends and processes that cause missing persons, causes and conditions of missing persons, results of police operations and special operations conduct. It is determined that the consolidation and combination of efforts of different units and services during the search work helps to increase the number of facts of locating missing persons. Attention is paid to the identification of factors influencing the assessment of the search work. The state of the international search for missing persons is analyzed. The necessity of using the positive experience of European countries in the outlined activities is substantiated.